Modelagem das perdas de solo por erosão hídrica em áreas tropicais brasileiras - Lense, Guilherme Henrique Expedito (2024)
Water erosion is the main cause of Brazilian soil degradation, and this problem must be constantly combated in order to guarantee soil conservation. In this context, modeling is a technique that can contribute to the planning of erosion mitigation practices. Therefore, the objective of the work was to model water erosion in five different Brazilian regions. In the first case, water erosion was evaluated in the Córrego Coroado sub-basin, in southeastern Brazil. The Erosion Potential Method (EPM) was applied to estimate water erosion between 1988 and 2018. The conversion of pasture and corn areas into coffee crops with the adoption of conservation practices and the expansion of reforestation areas contributed to a 37% reduction in soil losses. In the second case, the effect of deforestation on the spatial and temporal variation of water erosion in the Xingu River Basin, one of the regions most affected by deforestation in the Brazilian Amazon, was estimated. Between 1988-2018, there was an increase of 12% (52,258 km2 ) in the deforestation of the Amazon forest in the region, and using the EPM it was possible to verify that in this period there was a 312% increase in the rate of soil losses due to water erosion, which corresponding to around 180 million tons of soil. In the third case, water erosion was estimated in the Tietê River Basin using the Revised Universal Soil Loss Equation (RUSLE). In 18% of this territory, erosion rates are higher than the Soil Loss Tolerance Limits (T). In the fourth case, water erosion was estimated in the State of Rondônia, using RUSLE. The average rate of soil loss was 22.50 Mg ha-1 year-1 and 19% of the state's areas should be prioritized in the adoption of soil conservation measures. In the fifth case, soil losses were estimated in the Cantareira System, one of the largest water supply systems in the world. RUSLE pointed out that in 66% of the Cantareira System, soil losses are below T and, in 34% of the region, water erosion is compromising the sustainability of water and soil resources. In all regions studied there are areas with high soil losses associated with steep reliefs, soils with low density of vegetation cover, deforestation and lack of conservation practices. Modeling allows the identification of priority areas in the adoption of soil conservation management and is a way of highlighting the problem of soil degradation due to water erosion, raising awareness among public and private bodies about the need to mitigate erosion processes and encouraging the development and adoption environmental policies aimed at soil conservation.